2008
DOI: 10.1111/j.1468-3083.2008.02719.x
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional immunotherapy with killed Mycobacterium w vaccine for the treatment of ano‐genital warts: an open label pilot study

Abstract: Intralesional immunotherapy of ano-genital warts with Mw vaccine seems to be a promising new approach, which needs to be evaluated in the randomized controlled trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
125
3
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(142 citation statements)
references
References 10 publications
11
125
3
3
Order By: Relevance
“…The therapeutic response to intralesional MMR vaccine in our study was much higher than that reported by Kus et al 17 (29.4%), Clifton et al 18 (47%), King et al 19 (50%), Signore 20 (51%) and Horn et al 21 (53%), slightly higher than that reported by Johnson and Horn 22 (70.9%), similar to that reported by Phillips et al 23 (72%) and slightly lower than that reported by Johnson et al 24 (74%) , Brunk 25 (85%), Gupta et al 26 (88.9%) and Maronn et al 27 (87%). The presence of three synergistic viral antigens in MMR vaccine that could be associated with higher stimulation of the immune system may explain the relatively higher response in our study as compared to most of the related studies which utilize either a single antigen [17][18][19][20][21][22][23][24] or a combination of antigens.…”
Section: Discussioncontrasting
confidence: 46%
See 3 more Smart Citations
“…The therapeutic response to intralesional MMR vaccine in our study was much higher than that reported by Kus et al 17 (29.4%), Clifton et al 18 (47%), King et al 19 (50%), Signore 20 (51%) and Horn et al 21 (53%), slightly higher than that reported by Johnson and Horn 22 (70.9%), similar to that reported by Phillips et al 23 (72%) and slightly lower than that reported by Johnson et al 24 (74%) , Brunk 25 (85%), Gupta et al 26 (88.9%) and Maronn et al 27 (87%). The presence of three synergistic viral antigens in MMR vaccine that could be associated with higher stimulation of the immune system may explain the relatively higher response in our study as compared to most of the related studies which utilize either a single antigen [17][18][19][20][21][22][23][24] or a combination of antigens.…”
Section: Discussioncontrasting
confidence: 46%
“…Intralesional antigen injection probably induces strong non-specific inflammatory response against the HPV infected cells. 24,26 It has also been suggested that the trauma itself, or the bystander effect, may cause wart clearance in previously sensitized individuals. 17 Intralesional immunotherapy has been shown to be associated with release of different cytokines such as IL-2, IL-4, IL-5, IL-8, INF-c and TNF-a that stimulate a strong immune response against HPV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initially 0.1 ml is intradermally injected in the deltoids, followed by an intralesional injection at two weeks and is repeated weekly for a maximum of 10 weeks [15]. Photodynamic therapy is successfully being used albeit pending more conclusive results [16].…”
Section: Hiv+ Patientsmentioning
confidence: 99%